Discriminating ability of Cirrus and RTVue optical coherence tomography in different stages of glaucoma - Mittal, Deepti (Indian J Ophthalmol, 2018)
PURPOSE: The aim of this study is to determine which parameter of Cirrus and RTVue optical coherence tomography (OCT) has the highest ability to discriminate between early, moderate, and advanced glaucoma. Simultaneously, to compare the performance of the two OCT devices in terms of their ability to differentiate the three stages of glaucoma. Further, to analyze the macular parameters of both devices and compare them with the conventional retinal nerve fiber layer (RNFL) parameters. METHODS: One hundred and twenty eyes (30 healthy and 90 glaucomatous [30 mild, 30 moderate, and 30 advanced glaucoma]) of 65 participants (15 healthy, 50 glaucomatous [15 mild, 15 moderate, and 20 advanced glaucoma]) underwent Cirrus and RTVue OCT scanning on a single visit. RESULTS: Average RNFL thickness and superior RNFL thickness of both the devices and inferior (ganglion cell complex [GCC] of RTVue device best differentiated normals from all stage glaucomatous eyes (P > 0.05). Cirrus average RNFL thickness and superior RNFL thickness performed better than other parameters (P < 0.05) in differentiating early glaucoma from moderate and advanced. In differentiating advanced from early and moderate glaucoma, RTVue average, superior, and inferior RNFL thickness and inferior GCC parameters had the highest discriminating ability (P < 0.05). CONCLUSION: Overall, average RNFL thickness had the highest ability to distinguish different stages of the disease. No significant difference was found between RTVue and Cirrus OCT device in different severity levels. No significant difference was observed between RNFL and macular parameters in different stages of glaucoma.